Diasporas - Dufoix, Stephane; Rodarmor, William (Tr.) (Berkeley, 2008)
Coined in the third century B.C., the term diaspora has evolved into a buzzword used to describe the migrations of groups as diverse as ethnic populations, religious communities, and even engineers working abroad. This concise book provides a critical introduction to the concept of diaspora, bringing a fresh, synthetic perspective to virtually all aspects of this topic. Stephane Dufoix incorporates a wealth of case studies - about the Jewish, Armenian, African, Chinese, Greek, and Indian experiences - to illustrate key concepts, give a clear overview on current thinking, and reassess the value of the term for us today.
Keywords: Emigration and immigration